2008
DOI: 10.1111/j.1365-2915.2008.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of predatory fish exudates on the ovipostional behaviour of three mosquito species: Culex quinquefasciatus, Aedes aegypti and Culex tarsalis

Abstract: Three mosquito species, Culex tarsalis Coquillett, Culex quinquefasciatus Say and Aedes aegypti L. (Diptera: Culicidae), were examined in laboratory binary choice experiments to investigate whether fish exudates from the mosquitofish, Gambusia affinis (Baird & Girard) (Cyprinodontiformes: Poecilliidae), deter oviposition and whether the responses of these mosquito species to fish exudates in oviposition sites are consistent with the risk of predation from fish experienced by each species in their respective na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
2
33
1
2
Order By: Relevance
“…Intuitively, gravid females may avoid laying eggs on water that contains predator cues (Table 4). Indeed, cues from the mosquito fish Gambusia affinis Gaird & Girard (Angelon andPet ranka 2002, Van Dam andWalton 2008), the dragonfly predator Anax imperator Leach (Stav et al 1999), and the hemipteran predator Notonecta maculata Fabricius (Blaustein et al 2004) were found deterrent for mos quito oviposition. Furthermore, two compounds (n heneicosane and n tricosane) released by N. maculata induce oviposition avoidance in Culiseta longiareolata Macquart (Silberbush et al 2010).…”
Section: Cues From Mosquito Predatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively, gravid females may avoid laying eggs on water that contains predator cues (Table 4). Indeed, cues from the mosquito fish Gambusia affinis Gaird & Girard (Angelon andPet ranka 2002, Van Dam andWalton 2008), the dragonfly predator Anax imperator Leach (Stav et al 1999), and the hemipteran predator Notonecta maculata Fabricius (Blaustein et al 2004) were found deterrent for mos quito oviposition. Furthermore, two compounds (n heneicosane and n tricosane) released by N. maculata induce oviposition avoidance in Culiseta longiareolata Macquart (Silberbush et al 2010).…”
Section: Cues From Mosquito Predatorsmentioning
confidence: 99%
“…tarsalis experience high predation by G. affinis in nature and avoid laying eggs in containers with preda tor cues, while Ae. aegypti has low risk of predation by G. affinis in nature and shows no oviposition avoidance behavior (Van Dam and Walton 2008). Similarly, the wetland mosquito Culex tritaeniorhynchus Giles avoids cues of the predacious beetle Eretes griseus Fabricius, while Aedes albopictus Skuse, which do not share the same habitat, are not affected by these cues (Ohba et al 2012).…”
Section: Cues From Mosquito Predatorsmentioning
confidence: 99%
“…quinquefasciatus , but not Ae. aegypti , indicating that different species of mosquitoes have evolved to sense the predation risks in their natural habits [14]. Because oviposition of Ae.…”
Section: Predators For Mosquito Control—historical and Ongoing Stomentioning
confidence: 99%
“…Under laboratory conditions, B. splendens repelled A. aegypti females from laying eggs in the water where the fish were, but P. reticulata (Pamplona, et al 2009) and Gambusia affinis (Van Dam and Walton, 2008) did not. This repellency can be a problem because these fish cannot be very effective at controlling successive generations, especially when untreated oviposition sites are available (although in an integrated approach, those sites could be removed or treated with another control tool).…”
Section: Fishmentioning
confidence: 99%